What do clinical pharmacologists do? A questionnaire survey of senior UK clinical pharmacologists. - Aronson, J (2012)
Since the discipline expanded during 1970-1990, the number of UK consultant clinical pharmacologists has fallen. This paper describes the results of a questionnaire survey of the work patterns of 53 UK consultant clinical pharmacologists, including 35 (66%) employed by universities and 13 (25%) employed by the National Health Service (NHS). The range of activities undertaken includes: teaching medical students and others the principles of clinical pharmacology and practical therapeutics; research in a wide range of pharmacological and therapeutic areas; patient care, mostly in acute and general hospital medicine and in out-patient clinics; service both locally and nationally on a wide range of committees related to drug therapy; editorial work on learned journals and preparation of written teaching materials, including journal articles, didactic textbooks, reference books, and e-learning materials. The median amount of time that a UK consultant clinical pharmacologist spends on these activities is 50 hours per week; several work more than that. The time is spent as follows: teaching 10%; research 40%; clinical work 30%; policy and administration 12%; editorial work and writing 8%. The numbers of physicians who have been newly registered with the General Medical Council as clinical pharmacologists each year has so far been undiminished, but the number of consultant posts has fallen in 1990-2010. Many trainees therefore leave the discipline when they become consultants.